Magnetic graphene-based cyanopropyltriethoxysilane as an adsorbent for simultaneous determination of polar and non-polar organophosphorus pesticides in cow's milk. Issue 30 (4th March 2016) - Nodeh, Hamid Rashidi; Wan Ibrahim, Wan Aini; Sanagi, Mohd Marsin; Aboul-Enein, Hassan Y.
Abstract : A new adsorbent based on magnetic nanoparticles (Fe3 O4 ), graphene and cyanopropyltriethoxysilane was fabricated and applied to the magnetic solid phase extraction of organophosphorus pesticides. Abstract : A new adsorbent based on magnetic nanoparticles (Fe3 O4 ), graphene (G) and cyanopropyltriethoxysilane (CNPrTEOS) was fabricated and applied in the magnetic solid phase extraction (MSPE) of organophosphorus pesticides. The synthesized adsorbent was characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy and transmission electron microscopy. The Fe3 O4 @G–CNPrTEOS MSPE was used for the simultaneous preconcentration of four polar and non-polar organophosphorus pesticides namely phosphamidon, dimethoate, diazinon and chlorpyrifos in fresh cow's milk. Under optimum conditions, Fe3 O4 @G–CNPrTEOS MSPE shows good linearity in the concentration range of 0.1–200 ng mL −1, low limits of detection (0.01–0.6 ng mL −1 ) and high enrichment factors (2400). The precision of the MSPE method was investigated using intraday (% RSD 1.7–9.4%, n = 3) and interday (% RSD 10.7–17.6%, n = 15) studies. The synthesized adsorbent can be reused at least 10 times without significant loss of extraction efficiency. The Fe3 O4 @G–CNPrTEOS MSPE method offers good recovery (82–94%) for spiked milk samples as compared to commercial CNPr-SPE (42–59%) and C18-SPE (58–68%). The Fe3 O4 @G–CNPrTEOS MSPE method involves only dilution of the cow's milk analysed without any treatment prior to analysis, and fewer interferences from protein fractions were observed.